Dengue and yellow fever virus vectors: seasonal abundance, diversity and resting preferences in three Kenyan cities - Agha, Sheila B.; Tchouassi, David P.; Bastos, Armanda D. S.; Sang, Rosemary (Parasites & vectors, 2017)
Background The transmission patterns of dengue (DENV) and yellow fever (YFV) viruses, especially in urban settings, are influenced by Aedes ( Stegomyia ) mosquito abundance and behavior. Despite recurrent dengue outbreaks on the Kenyan coast, these parameters remain poorly defined in this and other areas of contrasting dengue endemicity in Kenya. In assessing the transmission risk of DENV/YFV in three Kenyan cities, we determined adult abundance and resting habits of potential Aedes ( Stegomyia ) vectors in Kilifi (dengue-outbreak prone), and Nairobi and Kisumu (no dengue outbreaks reported). In addition, mosquito diversity, an important consideration for changing mosquito-borne disease dynamics, was compared. Methods Between October 2014 and June 2016, host-seeking adult mosquitoes were sampled using CO 2 -baited BG-Sentinel traps (12 traps daily) placed in vegetation around homesteads, across study sites in the three major cities. Also, indoor and outdoor resting mosquitoes were sampled using Prokopack aspirators. Three samplings, each of five consecutive days, were conducted during the long-rains, short-rains and dry season for each city. Inter-city and seasonal variation in mosquito abundance and diversity was evaluated using general linear models while mosquito-resting preference (indoors vs outdoors) was compared using Chi-square test. Results Aedes aegypti , which comprised 60% ( n = 7772) of the total 12,937 host-seeking mosquitoes collected, had comparable numbers in Kisumu (45.2%, n = 3513) and Kilifi (37.7%, n = 2932), both being significantly higher than Nairobi (17.1%, n = 1327). Aedes aegypti abundance was significantly lower in the short-rains and dry season relative to the long-rains ( P < 0.0001). Aedes bromeliae , which occurred in low numbers, did not differ significantly between seasons or cities. Mosquito diversity was highest during the long-rains and in Nairobi. Only 10% ( n = 43) of the 450 houses aspirated were found positive for resting Ae. aegypti , with overall low captures in all areas. Aedes aegypti densities were comparable indoors/outdoors in Kilifi; but with higher densities outdoors than indoors in Kisumu and Nairobi. Conclusions The presence and abundance of Ae. aegypti near human habitations and dwellings, especially in Kilifi/Kisumu, is suggestive of increased DENV transmission risk due to higher prospects of human vector contact. Despite low abundance of Ae. bromeliae suggestive of low YFV transmission risk, its proximity to human habitation as well as the observed diversity of potential YFV vectors should be of public health concern and monitored closely for targeted control. The largely outdoor resting behavior for Ae. aegypti provides insights for targeted adult vector control especially during emergency outbreak situations.